Toxoplasma gondii isolates from chickens in an area with human toxoplasmic retinochoroiditis - Pardini, Lais Luján (2016)
The aim of this study was to detect, isolate and genetically characterize Toxoplasma gondii from tissues obtained from free range chickens which were breed in farms from patients with toxoplasmic retinochoroiditis in Misiones, Argentina. Thirty three samples of head (refrigerated = 18 and frozen = 15) from free range chickens were processed. Refrigerated (n = 18) chicken central nervous systems (CNS) were bioassay in mice. DNA was obtained from all samples (n = 33) and PCR was performed using TOX5-TOX8 T. gondii specific primers. Positive PCR samples were characterized by nested-PCR and restriction fragment length polymorphism using the markers SAG2, BTUB, GRA6, SAG3, PK1, L358, C22-8, C29-2 and Apico. T. gondii DNA was amplified in 30.3% (10/33) of CNS samples. Isolates were obtained in 27.7% (5/18) of inoculated CNS samples (TgCk11-9Arg, TgCk13-5Arg, TgCk14-5Arg, TgCk14-6Arg and TgCk14-7Arg). Seven samples showed a restriction pattern to all markers and were identified as atypical with several alleles type III. Genotyping of T. gondii from samples of patients with retinochoroiditis in the same area could improve the understanding of the epidemiology of toxoplasmosis in the region.